Calculation method and experimental study of coulomb friction coefficient in sheet metal forming. (June 2017) - Wang, Chunge; Ma, Rui; Zhao, Juan; Zhao, Jun
Abstract: Friction is one of the important factors influencing the formability of sheet metal and improving the forming quality. According to the relationship between the drawing force and the stroke, the linear fitting algorithm of the friction coefficient is given based on the least squares method. Based on the drawing die of the cylindrical parts, a friction coefficient measuring apparatus is developed, which has fixed calculation program. Through a series of deep drawing tests, the friction coefficients and force-stroke curves are measured for different combinations of sheet metal and lubricant. What's more, the drawing process of the cylindrical part with different specifications is carried out to examine the application of the measured friction coefficient. The results show that the friction coefficient calculated by the linear fitting algorithm can accurately reflect the friction state of the whole drawing process; the measurement of the friction coefficient is not limited by the size of the mould; the established test system, can be used for the measurement of friction coefficient in sheet metal forming.